Out-of-pocket payments for complementary medicine following cancer and the effect on financial outcomes in middle-income countries in southeast Asia: a prospective cohort study. Issue 3 (March 2022) - Kong, Yek-Ching; Kimman, Merel; Subramaniam, ShriDevi; Yip, Cheng-Har; Jan, Stephen; Aung, Soe; Khoa, Mai Trong; Ngelangel, Corazon A; Nyein, Htun Lwin; Sangrajrang, Suleeporn; Tanabodee, Jitraporn; Bhoo-Pathy, Nirmala; et al.
Summary: Background: Complementary medicine, which refers to therapies that are not part of conventional medicine, comprising both evidence-based and non-evidence-based interventions, is increasingly used following a diagnosis of cancer. We aimed to investigate out-of-pocket spending patterns on complementary medicine and its association with adverse financial outcomes following cancer in middle-income countries in southeast Asia. Methods: In this prospective cohort study, data on newly diagnosed patients with cancer were derived from the ASEAN Costs in Oncology (ACTION) cohort study, a prospective longitudinal study in 47 centres located in eight countries in southeast Asia. The ACTION study measured household expenditures on complementary medicine in the immediate year after cancer diagnosis. Participants were given cost diaries at baseline to record illness-related payments that were directly incurred and not reimbursed by insurance over the 12-month period after study recruitment. We assessed incidence of financial catastrophe (out-of-pocket cancer-related costs ≥30% of annual household income), medical impoverishment (reduction in annual household income to below poverty line following subtraction of out-of-pocket cancer-related costs), and economic hardship (inability to make necessary household payments) at 1 year. Findings: Between March, 2012, and September, 2013, 9513 participants were recruited into the ACTION cohort study, of whom 4754 (50·0%) participants were included in this analysis. Out-of-pocket expenditures on complementary medicine were reported by 1233 households. These payments constituted 8·6% of the annual total out-of-pocket health costs in lower-middle-income countries and 42·9% in upper-middle-income countries. Expenditures on complementary medicine significantly increased risks of financial catastrophe (adjusted odds ratio 1·52 [95% CI 1·23–1·88]) and medical impoverishment (1·75 [1·36–2·24]) at 12 months in upper-middle-income countries only. However, the risks were significantly higher for economically disadvantaged households, irrespective of country income group. Interpretation: Integration of evidence-supported complementary therapies into mainstream cancer care, along with interventions to address use of non-evidence-based complementary medicine, might help alleviate any associated adverse financial impacts. Funding: None.